2022
DOI: 10.3390/w14213394
|View full text |Cite
|
Sign up to set email alerts
|

History of Colonization of Jeju Island (Republic of Korea) by the Water Fleas (Crustacea: Cladocera) Is Reflected by the Seasonal Changes in Their Fauna and Species Associations

Abstract: The aim of this paper is to study the species composition, structure and seasonal dynamics of the cladoceran fauna and species associations in inland water bodies of Jeju Island (Republic of Korea). Only 47 taxa were found in 199 samples. Such faunal paucity could be explained by the existence of only a few types of aquatic environments on Jeju Island as compared to continental China and the Far East of Russia, with their great diversity of water types. We have demonstrated a high significance of the tropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 84 publications
2
8
0
Order By: Relevance
“…During the last decade, it was shown that the species composition of faunistic complexes of the Cladocera undergoes seasonal changes-even in the same water body [62]. In addition, we found that, in different lakes, similar functional associations (planktonic, phytal, and benthic) are represented by different taxa, and that the portion of endemics is significantly higher among the taxa involved in these associations.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…During the last decade, it was shown that the species composition of faunistic complexes of the Cladocera undergoes seasonal changes-even in the same water body [62]. In addition, we found that, in different lakes, similar functional associations (planktonic, phytal, and benthic) are represented by different taxa, and that the portion of endemics is significantly higher among the taxa involved in these associations.…”
mentioning
confidence: 58%
“…Note that even in a previous study it was shown that latitude alone, not longitude, is the main factor shaping the species composition in the region [36]. Furthermore, substantial seasonal differences in the cladoceran species abundance and association composition [62] forced us to use the samples collected at summer months only. As a result, we included in our analysis 422 qualitative samples from 343 water bodies taken in 2002-2021, from late June to earlier September.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The samples were put in 40% formalin, so that the concentration of the sample was 4%. The samples were identified with the help of trinocular and binocular microscopes, using generally accepted guides [9][10][11].…”
Section: Methodsmentioning
confidence: 99%